Shell Bed Identification of Kaliwangu Formation and its Sedimentary Cycle Significance, Sumedang, West Java - Aswan Aswan; S Rijani; Y. Riza (Geological Agency, 2013)
DOI: 10.17014/ijog.v8i1.151Kaliwangu Formation cropping out around Sumedang area contains mollusk fossils dominated by gastropods and bivalves. In terms of sequence stratigraphy, each sedimentary cycle generally consists of four shell bed types: Early Transgressive Systems Tract (Early TST) deposited above an erosional surface or sequence boundary, that is characterized by shell disarticulation, trace fossils, gravelly content, no fossil orientation direction, and concretion at the bottom; Late Transgressive Systems Tract (Late TST) identified by articulated (conjoined) specimen in its life position, that shows a low level abration and fragmentation, adult specimen with complete shells, and variation of taxa; Early Highstand Systems Tract (Early HST) characterized by adult taxa that was found locally in their life position with individual articulation, juvenile specimens frequently occured; Late Highstand Systems Tract (Late HST) determined as multiple-event concentrations, disarticulated shell domination, and some carbon or amber intercalation indicating terrestrial influence. Shell bed identification done on this rock unit identified nineteen sedimentary cycles.